Analize Die Casting process and Structure of HDF 12 Material for Lower Arm - Muhammad Yusuf Nurfani (Journal of Technology Informatics and Engineering, 2024)
Steel is part of raw material for manufacturing process making a product. Ferro Casting Ductile is part of manufacturing process from iron ore to be metal part using casting process. Die casting is a part of manufacturing process especially in automotive industries for engine of vehicle production process. this research will be focus on casting process, Ferro Casting Ductile (FCD). In this research using material steel HDF 12 Material, in this process production Magnesium, Pig Iron, Scrap, Silicon, Carburizer, Inoculant and Slagtol. Manufacturing process is melting process of all raw material using temperature (melting point) at 1100 - 1400 ºC. When Specimen finish to process production will be analyze using spicrometer and SM machine for check of characteristic material and structure for crack issue. The result show that after casting process, the HDF12 have composition rate iron (Fe) content, namely 93.37% and also carbon (C) 3.82% and silicon (Si) 2.31% after check using. As visual check after die casting, lower arm is there no any crack, flash, flow mark finding by visual check inspection result. SEM Measurement check result until 300μm the result show that no any finding crack issue and result of Tensile strength of material Lower Arm upper limit is 433Kgf/cm2 and lower limit is 420 Kgf/cm and Elongation is 32%.